2015
DOI: 10.7314/apjcp.2014.15.24.10841
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Shisha and Cigarette Smoking in the General Population in Malaysia

Abstract: Background: Smoking is a primary risk factor for cancer development. While most research has focused on smoking cigarettes, the increasing popularity of shisha or water pipe smoking has received less attention. This study measured the prevalence and risk factors for shisha and cigarette smoking and related knowledge. Materials and Methods: This cross-sectional analytical study was conducted in Shah Alam, Malaysia. Participants aged ≥ 18 years were selected from restaurants. Data regarding demographic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
1
22
4
Order By: Relevance
“…Al-Naggar et al, studied the pattern, related knowledge and risk factors for shisha smoking among Malaysians 7 . They concluded that Malaysians had relatively low knowledge about shisha smoking and the prevalence of shisha smoking was high among Malaysians 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Naggar et al, studied the pattern, related knowledge and risk factors for shisha smoking among Malaysians 7 . They concluded that Malaysians had relatively low knowledge about shisha smoking and the prevalence of shisha smoking was high among Malaysians 7 .…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that Malaysians had relatively low knowledge about shisha smoking and the prevalence of shisha smoking was high among Malaysians 7 . Al-Naggar et al, also studied the associated risk factors for shisha smoking among University students.…”
Section: Resultsmentioning
confidence: 99%
“…The following socio-demographic correlates were considered: gender, age (categorized as [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 55 years or more); education (0-4, 5-8, 9-11, 12 years or more, respectively defined as low, low-average, high-average, and high); marital status (married/cohabiting, previously married [separated/divorced/widowed], never married); employment (working/student, homemaker, retired, unemployed/other);…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…There is the need to explore the applicability of DSM and ICD diagnostic approaches in different populations, such as Brazil, because studies have found different trends and correlates of tobacco smoking in Low-and Middle-Income countries (LMIC) [25,26,27]. For instance, the relationship between smoking and socio-economic correlates in LMIC countries seems to be different from that seen in Upper-Income countries [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation